Wyznaczenie warunków dla określenia wstępnej izolinii zasięgu zanieczyszczeń jako element monitoringu środowiska wokół Huty Miedzi "Głogów" = Monitoring of agricultural environment condition on the peripheries of former protection zone of the Copper Smelter "Głogów" - Rosada, Janusz; Przewocka, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The mining and metallurgical activity in the Legnica-Głogów Industrial District, resulting from the presence of rich deposits of copper ore, caused significant environmental pollution with heavy metals. Copper Smelter GŁOGÓW located at a distance of 7 km northwest from the Głogów city, being one of the biggest industrial plants in the area, significantly supported the economic development of the region, but also contributed to a number of unfavourable changes in the natural environment.
Keywords: huta miedzi; metale ciężkie; środowisko rolnicze; gleba; zanieczyszczenie gleb; copper smelter; heavy metals; agricultural environment; soils; pollution